Variability of interferon-γ release assays in people at high risk of tuberculosis infection or progression to tuberculosis disease living in the United States. (July 2022) - Winglee, Kathryn; Hill, Andrew N.; Belknap, Robert; Stout, Jason E.; Ayers, Tracy L.
Abstract: Objectives: Interferon-γ release assays, including T-SPOT. TB (TSPOT) and QuantiFERON Gold In-Tube (QFT), are important diagnostic tools for tuberculosis infection, but little work has been done to study the performance of these tests in populations prioritized for tuberculosis testing in the United States, especially those other than health care personnel. Methods: Participants were enrolled as part of a large, prospective cohort of people at high risk of tuberculosis infection or progression to tuberculosis disease. All participants were administered a tuberculin skin test, TSPOT, and QFT test. A subset of participants had their QFT ( n  = 919) and TSPOT ( n  = 885) tests repeated when they returned to get their tuberculin skin test read 2 to 3 days later (repeat study). A total of 531 participants had a TSPOT performed twice on the same sample taken at the same time (split study). Results: The QFT repeat test interpretations were discordant (one test positive and the other negative) for 6.4% of participants (59 of 919), and the TSPOT tests were discordant for 60 of 885 participants in the repeat study (6.8%) and 41 of 531 participants in the split study (7.7%). There was a high degree of variability in the quantitative test results for both QFT and TSPOT, and discordance was not associated with both test results being near the established cut-offs. Furthermore, the proportion of discordance was similar when comparing participants in both the TSPOT repeat and TSPOT split studies. Discussion: Both QFT and TSPOT were 6% to 8% discordant. The results should be interpreted with caution, particularly when seeing a conversion or reversion in serial testing.